2020
DOI: 10.3390/cancers12040802
|View full text |Cite
|
Sign up to set email alerts
|

ER and PI3K Pathway Activity in Primary ER Positive Breast Cancer Is Associated with Progression-Free Survival of Metastatic Patients under First-Line Tamoxifen

Abstract: Estrogen receptor positive (ER+) breast cancer patients are eligible for hormonal treatment, but only around half respond. A test with higher specificity for prediction of endocrine therapy response is needed to avoid hormonal overtreatment and to enable selection of alternative treatments. A novel testing method was reported before that enables measurement of functional signal transduction pathway activity in individual cancer tissue samples, using mRNA levels of target genes of the respective pathway-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 52 publications
(91 reference statements)
0
28
0
Order By: Relevance
“…cancer pathophysiology and to predict prognosis and response to therapy van Boxtel et al, 2019;Inda et al, 2020;Sieuwerts et al, 2020;van Weelden et al, 2020). A few key results are summarized below, centered around the role of the different signaling pathways in the various cancer types.…”
Section: Application Of the Mrna-based Assay Platform To Measure Activity Of Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…cancer pathophysiology and to predict prognosis and response to therapy van Boxtel et al, 2019;Inda et al, 2020;Sieuwerts et al, 2020;van Weelden et al, 2020). A few key results are summarized below, centered around the role of the different signaling pathways in the various cancer types.…”
Section: Application Of the Mrna-based Assay Platform To Measure Activity Of Signaling Pathwaysmentioning
confidence: 99%
“…Pathway analysis in three independent clinical studies (performed using both Affymetrix microarrayand qPCR-based pathway analysis) showed that in primary ER positive breast cancer patients, the ER pathway activity score predicted response to neoadjuvant treatment with an aromatase inhibitor (Inda et al, 2020). In ER positive breast cancer patients who developed metastatic disease and were subsequently treated with first line tamoxifen, an active ER pathway was associated with a better prognosis (Sieuwerts et al, 2020). In both ovarian cancer and endometrial cancer, loss of ER pathway activity was associated with higher grade cancer type and worse prognosis (van Lieshout et al, 2020;van Weelden et al, 2020).…”
Section: Application Of the Mrna-based Assay Platform To Measure Activity Of Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach used to develop tests to measure activity of signal transduction pathways is based on measuring the mRNA levels of target genes of the pathway-specific transcription factor and has been described before (6)(7)(8)(16)(17)(18)(19)(20). Target genes that were identified and used to develop the JAK-STAT1/2 models and the JAK-STAT3 models are listed in Supplementary Table S1.…”
Section: Development and Validation Of The Jak-stat1/2 And Jak-stat3 mentioning
confidence: 99%
“…We describe development, as well as evaluation in preclinical and clinical studies, of an mRNAbased test to quantify the immune response to a viral infection, based on measuring activity of the JAK-STAT1/2 and JAK-STAT3 signal transduction pathways in a whole blood or Peripheral Blood Mononuclear Cell (PBMC) sample, or in separate immune cell types. The technology used to develop tests to measure activity of signal transduction pathways is based on measuring the mRNA levels of target genes of the pathway-specific transcription factor and has been described before (6), (7),(8),(9),(10),(11), (12) , (13).…”
Section: Introductionmentioning
confidence: 99%